Characterization of anatomy, lignin distribution, and response to pretreatments of sugarcane culm node and internode - Brienzo, Michel [UNESP]; Abud, Yuri; Ferreira, Solange; Corrales, Roberta C.N.R; Ferreira-Leitão, Viridiana S.; de Souza, Wanderley; Sant'Anna, Celso (Elsevier, 2016)
Sugarcane culm has different types of tissue organization, and its heterogeneity can influence the bagasse quality generated in the sugar/ethanol industry. The heterogeneity of the sugarcane bagasse contributes to the intrinsic recalcitrance of the biomass, impairing its conversion to ethanol. To determine the effects of sugarcane culm heterogeneity, the internode and node fractions were pretreated with acid, alkali, and peroxide. The investigation focused on the change in the fraction morphology, crystallinity, chemical composition, and enzymatic digestibility. Scanning electron microscopy (SEM) revealed different anatomical traits between the node and the internode. Vascular bundles appeared in larger number and diameter in the periphery of both the node and the internode. The internode and node responded differently to the pretreatments, with slight differences in the amount of hemicellulose and lignin removal. Furthermore, the internode was more susceptible to the acid and alkaline pretreatments than the node, generating a material with better digestibility. The fractions pretreated with peroxide showed similar enzymatic digestibility. In SEM images, the internode showed more structural damage after pretreatments than the node fibers. These results provide insight that pretreated sugarcane bagasse has fractions with different enzymatic digestibility related to their anatomy, and that conversion of the entire biomass is not feasible.
Keywords: Biomass anatomy; Biomass crystallinity; Cellulose digestibility; Pretreatment; Sugarcane node and internode